Retracted - Adil, Anam; Muhammad, Fida; Ishtiaq, Qasim; Rashid, Sana; Rashid, Hunza (Indus Journal of Bioscience Research, 2025)
The oral delivery and formulation of therapeutic peptide- and protein-based biopharmaceuticals continue to pose significant challenges within the pharmaceutical domain. These biomolecules exhibit inherently low oral bioavailability, primarily due to limited gastrointestinal solubility and permeability. Contributing factors include high molecular weight, poor membrane permeability, and extensive degradation by chemical and enzymatic processes within the gastrointestinal tract, all of which restrict their therapeutic potential. This review critically examines the barriers associated with oral administration of peptide/protein therapeutics and emphasizes the emerging role of lipid-based drug delivery systems (LBDDSs) specifically, solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) as innovative platforms to overcome these limitations. These lipid-based systems offer several pharmacokinetic and pharmacodynamic advantages, including protection against enzymatic degradation, improved drug solubility and absorption, enhanced mucosal permeability, reduced first-pass metabolism, and the potential for controlled and sustained release. The nanoscale size and modifiable surface properties of SLNs and NLCs further facilitate targeted delivery, prolonged systemic circulation, and improved therapeutic index. LBDDSs are characterized by favorable features such as ease of fabrication, scalability, biodegradability, biocompatibility, low systemic toxicity, and the ability to encapsulate both hydrophilic and lipophilic agents. These attributes collectively underscore their promise in enhancing oral bioavailability and therapeutic efficacy of peptide/protein-based drugs. Despite these advantages, critical formulation challenges particularly those related to plasma stability, membrane translocation, and circulation half-life persist and require further investigation in future drug development efforts.